Sistem Informasi Inventarisasi Sarana dan Prasarana Sekolah (STUDI KASUS: Madrasah Tsanawiyah Muhammadiyah Surakarata) - Nastiti, Faulinda Ely; Kusumawati, Novi (Jurnal Sistem Komputer, 2014)
Inventory of facilities and infrastructure must be managed well by schools or madrassas. That is because the infrastructure is one element of assessment in school or madrasah accreditation. Therefore, the inventory system infrastructure in schools should be standardized in accordance with the legislation in force. Inventory system infrastructure built on MTs Surakarta in detail in accordance with the standard format using Code Igniter Framework. The results of this study are the Infrastructure Inventory Information System which can be used as a medium for data penginventarisasian school infrastructure that contains, among others, the encoding inventory, data inventory of land, buildings or building a data inventory, data inventory and machinery and equipment